International Conference on Ship Motions and Manoeuvrability, London, 18 & 19 February 1998 : [proceedings] - International Conference on Ship Motions and Manoeuvrability (1998 : London); Royal Institution of Naval Architects (London : RINA Conference Proceedings, 1998)
19